Absence of methicillin-resistant Staphylococcus aureus (MRSA) in cattle from Portugal - Correia, Susana (2020)
This work was funded by the R&D Project CAREBIO2 - Comparative assessment of antimicrobial resistance in environmental biofilms through proteomics - towards innovative theranostic biomarkers, with reference NORTE-01-0145-FEDER-030101 and PTDC/SAU-INF/30101/2017, financed by the European Regional Development Fund (ERDF) through the Northern Regional Operational Program (NORTE 2020) and the Foundation for Science and Technology (FCT). This work was supported by the Associate Laboratory for Green Chemistry - LAQV which is financed by national funds from FCT/MCTES (UID/QUI/50006/2019). Vanessa Silva is supported by national funds through FCT/MCTES and by the European Social Fund through POCH/FSE under the PhD grant SFRH/BD/137947/2018.